Healthy Minds for Healthy Hearts: Tackling Stress-Induced Cardiac Events During the FIFA World Cup 2022 - Muna Abed Alah (14779534) (2022)
Millions of people are looking forward to the biggest event this year “FIFA World Cup 2022” taking place in the state of Qatar. This event is an opportunity for people around the world to socialize, connect, celebrate, and enjoy watching football matches. However, the emotional stress experienced by football players and fans during a such major sport event can sometimes result in unfavorable physiological responses that can adversely affect the heart leading to adverse cardiac consequences. In this mini-review, we summarized the evidence and pathophysiology of stress-induced cardiac events during football games, and the potential strategies to prevent stress-induced cardiac events during the FIFA World Cup 2022. Other Information Published in: Vascular Health and Risk Management License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/vhrm.s390549